2023
DOI: 10.3390/life13010151
|View full text |Cite
|
Sign up to set email alerts
|

Spherocytosis-Related L1340P Mutation in Ankyrin Affects Its Interactions with Spectrin

Abstract: Previously, we reported a new missense mutation in the ANK1 gene that correlated with the hereditary spherocytosis phenotype. This mutation, resulting in L1340P substitution (HGMD CM149731), likely leads to the changes in the conformation of the ankyrin ZZUD domain important for ankyrin binding to spectrin. Here, we report the molecular and physiological effects of this mutation. First, we assessed the binding activity of human β-spectrin to the mutated ZZUDL1340P domain of ankyrin using two different experime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…In our previous study, we reported new variants in the genes correlated with the hereditary hemolytic anemia phenotype including HS in a few Polish families [ 37 , 38 , 39 , 40 , 41 ]. In this report, we presented a Polish family with a novel missense mutation in the SLC4A1 gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we reported new variants in the genes correlated with the hereditary hemolytic anemia phenotype including HS in a few Polish families [ 37 , 38 , 39 , 40 , 41 ]. In this report, we presented a Polish family with a novel missense mutation in the SLC4A1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Used predefined data based on information deposited in biological databases and in the literature may not take into account undescribed and unverified facts for specific variants in genes that have not yet been linked to clinical symptoms or molecular mechanisms. It should also be mentioned that experimental verification of the functional effect of the observed mutation is not always relatively easy to perform, as our team did in the case of the ankyrin variant (p.L1340P) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%